HUBUNGAN ANTARA RIWAYAT PENYAKIT JANTUNG DENGAN TINGKAT KEPARAHAN STROKE ISKEMIK AKUT PERTAMA KALI - Ignatius Ivan; Budi Riyanto Wreksoatmodjo; Octavianus Darmawan (NEURONA, 2019)
ASSOCIATION BETWEEN HISTORY OF HEART DISEASE AND SEVERITY OF ACUTE FIRST-EVER ISCHEMIC STROKEABSTRACTIntroduction: History of heart disease such as atrial  fibrillation, angina pectoris, myocardial infarction, heart failure has a role on ischemic stroke severity.Aim: This research aims to find the association between history of heart disease and stroke severity using NIHSS score on acute ischemic stroke patients in Atma Jaya hospital during 2014-2018.Method: This research used cross-sectional method with two-sided fisher’s exact test. With total sampling, samples retrieved from secondary sources in Atma Jaya hospital during 2014-2018 resulting 236 subjects. Stroke severity measured by NIHSS score during admission, categorized with severe stroke (15-42) and non-severe stroke (0-14).Result: There is a significant association between history of AF (p=0.046) on first-ever ischemic stroke severity. Acute first-ever ischemic stroke patients who are  >18 years old with history of AF has a tendency of 5,2 times to have severe stroke compared with patients without AF. Other history of heart disease has no significant association towards stroke severity.Discussion: In accordance with previous research, our findings suggest a significant association between history of atrial fibrillation and acute first-ever ischemic stroke severity in which there is a tendency of more severe stroke compared wth patients without AF. Unlike previous findings, this research shows no significant association between history of heart failure and stroke severity due to limited data characteristic  of ejection fraction preventing us to include patient with ejection fraction below 30%. This limitation may also allow history of angina pectoris and myocardial infarction to be insignificant.Keywords:  Atrial  fibrillation,  heart  failure,  ischemic  stroke,  myocardial  infarction,  National  Institutes  of Health Stroke ScaleABSTRAKPendahuluan: Riwayat penyakit jantung seperti atrial fibrilasi, angina pektoris, infark miokardium, gagal jantung memiliki peran terhadap keparahan stroke iskemik.Tujuan: Mengetahui hubungan riwayat penyakit jantung dengan tingkat keparahan stroke berdasarkan skor NIHSS pada pasien stroke iskemik akut di RS Atma Jaya pada tahun 2014-2018.Metode: Penelitian potong lintang terhadap data sekunder pasien stroke iskemik pertama kali yang dirawat di RS Atma Jaya pada tahun 2014-2018. Keparahan stroke diukur berdasarkan National Institutes of Health Stroke Scale (NIHSS) masuk dengan kategori severe stroke (skor 15-42) dan non-severe stroke (0-14). Dilakukan uji Fisher dua sisi untuk menilai hubungan.Hasil: Terdapat 236 subjek dengan mayoritas hubungan riwayat AF (p=0,046) terhadap tingkat keparahan stroke. Pasien berumur >18 tahun yang mengalami stroke iskemik akut pertama kali dengan riwayat AF akan berpeluang 5,2 kali lebih tinggi untuk mengalami severe stroke dibandingkan jika tanpa riwayat AF. Riwayat penyakit jantung lain tidak memiliki hubungan signifikan terhadap tingkat keparahan stroke.Diskusi: Terdapat hubungan yang signifikan antara riwayat AF terhadap tingkat keparahan stroke, terutama pada subjek dengan severe stroke jika dibandingkan pasien tanpa riwayat AF. Tidak ditemukan hubungan signifikan antara penyakit jantung yang lain dikarenakan keterbatasan data penelitian.Kata kunci: Atrial fibrilasi, gagal jantung, infark miokardium, National Institutes of Health Stroke Scale, stroke iskemik